Acceptance of technology in oil palm plantation among smallholders in Ulu Cheka, Jerantut, Pahang / Hafizi Ahmad Saharudin - Ahmad Saharudin, Hafizi (Faculty of Plantation and Agrotechnology, 2017)
Agriculture engineer has invented various types of technology in oil palm industry to be implemented in oil palm plantation to minimize cost and increasing yield. Many research has conducted in this sector, but still the industry is in the need the most suitable and cheaper technology. Thus, to meet the demand of suitable technology to use in the oil palm plantation the study of acceptance of technology among smallholders has been conducted. The survey was conducted and the questionnaire was distributed among smallholders in Ulu Cheka,Jerantut, Pahang. The population in this study is 100 samples and the respondent are 80. This study has listed that perceived ease of use, perceived usefulness; self-satisfaction and cost are the most influences factor in acceptance of technology. The data analyse using Statistical Package for Science Social (SPSS). From the data analysis, researcher have found that all the factors have moderate and significant relationships and only two of the factor which is perceived ease of use and cost of technology influencing the acceptance of technology in oil palm plantation among smallholders. These become the challenge for agriculture engineer to invent the suitable and cheaper technology to attract potential adopter in future.